SCIENTIFIC RESEARCH OF CLEANING OF SALT LAYERS OF COAL PROCESSING EQUIPMENT USED FOR OBTAINING FUEL FROM COAL AND PLANT WASTE - KUCHAROV, Azizbek; MAMANAZAROV, Murodali; XALILOV, Sanjar (Journal of Experimental Studies, 2024)
In this article, samples were taken from brine layers of heat exchangers and coal reprocessing equipment and their chemical composition was determined using various methods. In addition, the results of the atomic absorption spectrophotometer (AAC-spectrum) related to NaX zeolite are presented. The results of chemical analysis of entities formed in the device created for the process of obtaining liquid fuel obtained from coal and factory waste have been scientifically studied. In order to obtain high-quality coal products, it is necessary to develop the technology of coal enrichment in a complex way. For this purpose, a new flotation reagent will be developed, its physicochemical properties, efficiency in flotation enrichment, and coal gas extraction technology require development. In these processes, there are layers of salt, and it is necessary to develop chemical reagents that dissolve these layers in a complex manner. Preliminary scientific results were obtained for this and presented in this article.